Fractured - Terry, Teri (New York Nancy Paulsen Books, 2013)
Although Kyla has recovered some of her memories, she is not sure how they all fit together, whether she was really a terrorist, or why she is able to remember anything at all from before she was "slated"--but she is determined to find the answers
Keywords: Memory -- Terrorism -- Identity (Psychology)